ANALISIS PROFIL KONSUMEN UNTUK APLIKASI MARKET PLACE PRODUK FURNITUR KAYU JATI - Malau Asima Fryani; Kristina Sisilia (Fakultas Ekonomi dan Bisnis, 2020)
On globalization era, there is a growing desire of consumers who want everything to be easy to meet their needs and desires, so there are now a lot of marketplace application that have sprung up where the application can facilitate consumers. One of the job is to buy furniture. Phenomenon is found that there is not marketplace application espessially for sells teak wood furniture. The aims of this research is to find out how is the customer profile is the which includes perceptions and expectations for the user segment teak wood furniture using marketplace application.This research is decriptive with qualitative approach. The technique of collecting data is interview, observation dan documentation. The study using design canvas value proposition by Alexander Osterwalder and Yves Pigneur to determine customer profile. In this research customer perceptions and expectations is a original product, guarantee of warranty, easy payment method, the application easy to use and understand, valid information, fitur and interested design, admin fast response, minimal error occurred, no ads often appear, do not feel loss, updates on new products, save time, save money, and application is released soon..